Contribution of Basic Education to Earth Governance Systems and Future Social Sciences - Khairunnas, Khairunnas; Alpusari, Mahmud; Amrifo, Victor (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Scientific literacy has become a fundamental focus of Education and is related to the ability to criticize scientific discussions. From the beginning we are required to be able to make decisions by individuals and have a sense of responsiveness to public issues related to science but do not rule out access to get it all must be good both in terms of learning in elementary school. Learning is divided into two, namely conventional and problem-based learning based on scaffolding. The result of this article is the need to increase mathematical modeling skills in students with a problem-based learning approach is higher than conventional. So, Problem based learning will certainly have a positive effect to tackle global warming by applying five main challenges and correlating the relationship of the earth's governance system to social science with elementary education input as the spearhead of generational change for the better.